Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T22:57:35+01:00
Dla m=1:
-4x + 3 > 0
-4x > -3
x < 3/4
x∈(-∞, 3/4)

dla m≠1:
Δ=16-4(m-1)(m+2) = 16-4(m²+m-2)=16-4m²-4m+8 = -4m²-4m+24

Δ₁=16+16*24 = 400, √Δ₁=20
m=(4-20)/(-8)=2 ∨ m=(4+20)/(-8)=-3

Δ>0 <=> m∈(-3, 2)
Δ=0 <=> m∈{-3, 2}
Δ<0 <=> m∈(-∞, -3)u(2, ∞)

dla Δ<0 ∧ m-1>0 rozwiazaniem bedzie x∈R
m∈(-∞, -3)u(2, ∞) ∧ m>1
m∈(2, ∞)

dla Δ≤0 ∧ m-1<0 rozwiazaniem bedzie zbior pusty
m∈(-∞, -3>u<2, ∞) ∧ m<1
m∈(-∞, -3>

dla Δ=0 ∧ m>1
m=2
x₁=x₂=4/2 = 2
x∈R\{2}

dla Δ>0 ∧ m>1
m∈(1, 2)
√Δ = √(-4m²-4m+24) = √(-4(m-2)(m+3)) = 2√(2-m)(m+3)
x₁=(4-2√(2-m)(m+3))/(2(m-1)) = (2-√(2-m)(m+3))/(m-1)
x₂=(2+√(2-m)(m+3))/(m-1)
x∈(-∞, x₁)u(x₂, ∞)

dla Δ>0 ∧ m<1
m∈(-3, 1)
x∈(x₁, x₂)

podsumowujac:
m∈(-∞, -3> to brak rozwiazan
m∈(-3, 1) to x∈(x₁, x₂)
m=1 to x∈(-∞, 3/4)
m∈(1, 2) to x∈(-∞, x₁)u(x₂, ∞)
m=2 to x∈R\{2}
m∈(2, ∞) to x∈R